MANAJEMEN KOMUNIKASI BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) TERHADAP BENCANA BANJIR DI KABUPATEN KAMPAR - Saputra, Erwind; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Communication management has a very important role to overcome the problem of disaster and also to prevent and reduce the impact of disasters. Communication management in question is the management of disaster management that involves the process of communication, coordination between the community and the government for the handling of disaster victims run effectively and efficiently. In disaster management, the presence of BPBD is an important element in providing disaster information, rescue, and disaster recovery with good coordination and communication, this will encourage the smooth handling of any future disasters, especially to the flood disaster that hit Kampar district.The type of research is qualitative with the presentation of descriptive analysis. Data collection techniques through observation, interview and documentation.. This study focuses on the communication management of the Badan Penanggulangan Bencana Daerah (BPBD) against flood disasters in Kampar regency. For the purpose of this study, the following four questions are proposed: (1) How to plan BPBD communication on flood disaster in Kampar regency (2) How to organize BPBD communication against flood disaster in Kampar regency (3) How to implement BPBD communication against flood disaster in Kampar regency (4 ) How to evaluate BPBD communication to flood disaster in Kampar regency.The results of this study indicate that (1). BPBD communication planning against flood disaster in Kampar regency is arranged in Renja and Renstra BPBD Kampar Regency. (2) Organizing BPBD communications against flood disaster in Kampar regency, formally prepared (3) Implementation of BPBD communication against flood disaster in Kampar regency, carried out by a special field called Pusdalops-pb which has a special unit that is TRC (Team Reaksi Cepat (4) Evaluation of BPBD communications against flood disaster in Kampar regency, conducted every day in case of disaster, if not the occurrence of disaster BPBD Kampar District conducts evaluation activities at monthly meetings, annual meetings and impromptu meetings done in the event of a disaster.Keywords: Communication Management, Badan Penanggulangan Bencana Daerah (BPBD) Kabupaten Kampar, flood disaster